THE ROLE OF POSTHARVEST MACHINERIES AND PACKAGING IN MINIMIZING AFLATOXIN CONTAMINATION IN PEANUT - Paramawati, Raffi; Widodo, Puji; Budiharti, Uning; ., Handaka (Indonesian Agency for Agricultural Research and Development - MOA, 2006)
As a tropical country with relatively high humidity and temperature, Indonesia is struggling with aflatoxin which frequently contaminates peanut. Aflatoxin is a carcinogenic toxic substance that could cause liver cancer. Due to the increasing concern on food safety, the Indonesian Drugs and Foods Agency specifies the maximum aflatoxin allowed in peanut as much as 20 ppb. However, researches showed that aflatoxin contamination in peanut in Indonesia is much higher than the threshold. The study was carried out to observe the effect of using postharvest machineries and packagingÂ treatments on aflatoxin contamination in peanut. Reduction of postharvest processes was conducted by using series of machineries, e.g. thresher, dryer, and sheller. Packaging treatments, e.g. vacuum plastic pack, hermetic glass chamber, and polyethylene (PE) plastic wrap were carried out during storage at ambient temperature (25-27Â°C). The results showed that using machineries in postharvest handling produced peanut free from aflatoxin contamination. However, without effective packaging, the aflatoxin level would increase during storage. Hermetic packaging could protect peanut from the mold as indicated by low level of aflatoxin contamination.